Sharing digital trace data: Researchers’ challenges and needs - Jan Schwalbach; Reiner Mauer (Big Data & Society)
Over the past decade, research has made rapid progress in the collection and analysis of digital trace data. However, when it comes to sharing data, researchers still face major barriers that often limit or prevent the reproducibility of research results and the reuse of data. Against this backdrop, we identify three broader categories of user challenges, namely researchers’ capacities & incentives, legal & ethical challenges, and technical hurdles. We describe in detail the problems researchers face in each category and why these often prevent researchers from sharing data, thus limiting both the reproducibility of research outputs and data reuse in other research projects. We conclude each category with specific needs of researchers for sharing digital trace data and making it reusable for others. These are intended to provide researchers as well as research institutes and repositories with approaches to improve the situation of data sharing.